Parasitic Contamination of raw vegetables sampled from different farm locations in Brack Al-Shati, Libya - Shaheerah Alsounosi Alshareef, Awatif M. Abdulsalam, Rajaa Abobaker Alghanaei, Eljelani S. Salim and Mohamed Chibani (Journal of Pure & Applied Sciences, 2019)
Background: Fresh Vegetables provide important nutritional value for humans; however, consumption of raw vegetables can be a major route for transmission of food-borne parasitic diseases. Hence, this study aimed to investigate the parasitic contamination of commonly consumed local vegetables in Brack Al-Shati, Libya. Methods: A total of 200 samples of fresh vegetables were randomly collected from vegetable farms in Brack Al-Shati, Libya. The vegetables included; green onion, lettuce, rocket, coriander, parsley, chard, mint, cucumber, carrot, tomato, and turnip. Samples were washed in saline, and the resulting washing solution was filtered and centrifuged to concentrate the parasitic stages. The sediments were examined by iodine and modified Ziehl-Neelsen stained smears. Results: The percentage of contamination was 33.0% (66/200), with predominance of nematode larvae (37.9 %), eggs of Ascaris (22.7%), cysts of Entamoeba spp. (18.2%), oocysts of Cryptosporidium spp. (16.7%), cysts of Giardia lamblia (3.0%) and eggs of Hymenolepis nana (1.5%). The highest number of contaminated samples was detected in rocket (70.1%) while the least number of contaminated samples was detected in green onion (6.7%). No parasite was detected in tomato samples. Conclusion: The study highlighted the importance of vegetables as the potential source for transmission of intestinal parasites to humans. Vegetables contaminated with the pathogenic parasites may pose health risk to the consumers if consumed without proper cleaning and or cooking.